2011
DOI: 10.3390/ijms12053072
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Aminoethylcysteine Ketimine Decarboxylated Dimer: A Review

Abstract: Aminoethylcysteine ketimine decarboxylated dimer is a natural sulfur-containing compound detected in human plasma and urine, in mammalian brain and in many common edible vegetables. Over the past decade many studies have been undertaken to identify its metabolic role. Attention has been focused on its antioxidant properties and on its reactivity against oxygen and nitrogen reactive species. These properties have been studied in different model systems starting from plasma lipoproteins to specific cellular line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 80 publications
2
9
0
Order By: Relevance
“…6 work has suggested that AECK-DD is generated from serine and cysteine by the action of cystathionine β-synthase. 7,8 Our findings of increased brain AECK-DD in rats treated with high doses of cysteamine is consistent with this hypothesis. 7 Moreover, mice deficient in transporters for cysteamine have less cerebral AECK-DD than control littermates.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…6 work has suggested that AECK-DD is generated from serine and cysteine by the action of cystathionine β-synthase. 7,8 Our findings of increased brain AECK-DD in rats treated with high doses of cysteamine is consistent with this hypothesis. 7 Moreover, mice deficient in transporters for cysteamine have less cerebral AECK-DD than control littermates.…”
supporting
confidence: 88%
“…However, there appears to be considerable species variability because, in the same study, AECK-DD was detectable in mouse brain at a content of ∼1 nmol/g wet weight (∼1.2 μmol/L) . Previous work has suggested that AECK-DD is generated from serine and cysteine by the action of cystathionine β-synthase. , Our findings of increased brain AECK-DD in rats treated with high doses of cysteamine is consistent with this hypothesis . Moreover, mice deficient in transporters for cysteamine have less cerebral AECK-DD than control littermates …”
supporting
confidence: 87%
“…Furthermore, we detected evidence of oxidative stress in the aggressive brain, i.e. a significant increase in the marker nitrotyrosine (P < 0.01; t(34) = 3.56) and decreases in the antioxidants taurine and glutathione (Macone et al 2011) (P < 0.09; t(23.8) = −1.74; Fig. S2).…”
Section: Figure 1: Differential Expression Of Glycolysis Andmentioning
confidence: 93%
“…AECK-DD has been reported to be an anti-oxidant at μM-concentrations and it has been suggested that this compound may be active in vivo [12–16]. Given this suggestion, and the considerable interest in the scientific and lay communities regarding natural anti-oxidants as possible therapeutic agents and as research tools, we were interested in developing a highly sensitive analytical approach for the measurement of AECK-DD.…”
Section: Introductionmentioning
confidence: 99%